Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) (25x5 – 5x4 + 10x2) : 5x2 = (25x5 : 5x2 ) - (5x4 : 5x2 ) + (10x2 : 5x2 )
= 5x3 – x2 + 2
b) (15x3y2 – 6x2y – 3x2y2) : 6x2y
= (15x3y2 : 6x2y) + (– 6x2y : 6x2y) + (– 3x2y2 : 6x2y)
= \(\dfrac{15}{6}\)xy - 1 - \(\dfrac{3}{6}\)y = \(\dfrac{5}{2}\)xy - \(\dfrac{1}{2}\)y - 1.
\(\frac{4xy-5}{10x^3y}-\frac{6y^2-5}{10x^3y}=\frac{\left(4xy-5\right)-\left(6y^2-5\right)}{10x^3y}=\frac{4xy-6y^2}{10x^3y}=\frac{2y\left(2x-3y\right)}{2y.5x^3}=\frac{2x-3y}{5x^3}\)
\(\left(\frac{2x+1}{2x-1}-\frac{2x-1}{2x+1}\right):\frac{4x}{10x-5}\)
\(=\frac{\left(2x+1\right)^2-\left(2x-1\right)^2}{\left(2x+1\right)\left(2x-1\right)}:\frac{4x}{10x-5}\)
\(=\frac{\left(2x+1+2x-1\right)\left(2x+1-2x+1\right)}{\left(2x+1\right)\left(2x-1\right)}\times\frac{10x-5}{4x}\)
\(=\frac{4x.2}{\left(2x+1\right)\left(2x-1\right)}\times\frac{5\left(2x-1\right)}{4x}\)
\(=\frac{10}{2x+1}\)
\(a,\frac{4xy-5}{10x^3y}-\frac{6y^2-5}{10x^3y}=\frac{\left(4xy-5\right)-\left(6y^2-5\right)}{10x^3y}=\frac{4xy-5-6y^2+5}{10x^3y}=\frac{4xy-6y^2}{10x^3y}\)
\(b,\left(\frac{2x+1}{2x-1}-\frac{2x-1}{2x+1}\right):\frac{4x}{10x-5}\)
\(=\left(\frac{2x+1}{2x-1}+\frac{2x-1}{2x-1}\right):\frac{4x}{10x-5}\)
\(=\frac{2x+1+2x-1}{2x-1}:\frac{4x}{10x-5}\)
\(=\frac{4x}{2x-1}.\frac{10x-5}{4x}\)
\(=\frac{10x-5}{2x-1}\)
\(=\frac{5\left(2x-1\right)}{2x-1}\)
\(=\frac{5}{1}=5\)
a) \(15x^3y^2+10x^2y^2-2x^3y^3\)
\(=x^2y^2\left(15x+10-xy\right)\)
b) \(-4x^3y-6x^2y^2-8x^4y^3\)
\(=-2x^2y\left(2x+3y+4x^2y^2\right)\)
c) \(3a\left(a+b\right)+2\left(a+b\right)^2\)
\(=\left(a+b\right)\left(3a+2a+2b\right)\)
\(=\left(a+b\right)\left(5a+2b\right)\)
d) \(16x^2-9\left(x+y\right)^2\)
\(=\left(4x-3x-3y\right)\left(4x+3x+3y\right)\)
\(=\left(x-3y\right)\left(7x+3y\right)\)
e) \(-a^2-2a-41\)
Sai đề
f) \(5\left(x-1\right)^3-10\left(1-x\right)^2\)
\(=5\left(x-1\right)^3+10\left(x-1\right)^3\)
\(=15\left(x-1\right)^3\)
a) \(x^2yz:xyz=\left(x^2:x\right)\left(y:y\right)\left(z:z\right)=x\)
b) \(x^3y^4:x^3y=\left(x^3:x^3\right)\left(y^4:y\right)=y^3\)
a) \(x^2+8x+15=x^2+3x+5x+15=\left(x+3\right)\left(x+5\right)\)
b) \(x^2+3x+2=x^2+2x+x+2=\left(x+1\right)\left(x+2\right)\)
c) \(-x^2+7x-6=-x^2+x+6x-6=\left(-x+6\right)\left(x-1\right)\)
d) \(5x^3y-10x^2y^2+5xy^3=5xy\left(x^2-2xy+y^2\right)=5xy\left(x-y\right)^2\)
e) \(2x^2+7x-15=2x^2-3x+10x-15=\left(2x-3\right)\left(x+5\right)\)
câu a nè = (4x-1)(2x-3)
câu f = (x+y+z) ( x^ 2 + y^2 + z^2 +xy + yz + zx)
a: \(=\dfrac{5\left(x^2+2xy+y^2\right)}{3\left(x^3+y^3\right)}\)
\(=\dfrac{5\left(x+y\right)^2}{3\left(x+y\right)\left(x^2-xy+y^2\right)}=\dfrac{5\left(x+y\right)}{3\left(x^2-xy+y^2\right)}\)
b: \(=\dfrac{x^2-4xy+4y^2-4}{2x\left(x-2y+2\right)}=\dfrac{\left(x-2y-2\right)\left(x-2y+2\right)}{2x\left(x-2y+2\right)}\)
\(=\dfrac{x-2y-2}{2x}\)
c: \(=\dfrac{2\left(x^2+5x+1\right)}{x\left(x-2\right)\left(x+2\right)}\)